ANALISIS KEPUASAN KERJA DAN LINGKUNGAN KERJA KARYAWAN DI SEKOLAH EN MANDARIN – MEDAN - WONG PONG HAN; ERVIRIANI .; ADE RAHMA AYU SIREGAR; IVONE .; LISA . (LP2MTBM MAKARIOZ, 2019)
Employee satisfaction should be created as the most in order to improve the moral work, dedication, love, and discipline ofemployees. The method used in this research is a qualitative method with the technique of collecting research data is withinterviews. The analysis of the data used is according to Miles and Huberman, namely by data reduction, data presentation,and withdrawal of conclusions. The purpose of this research is to know the satisfaction of employee work at EN MandarinSchool. Based on the results of the research on employees ' work satisfaction at EN Mandarin School Medan, it can beconcluded that the interaction between employees in EN Mandarin goes well, the relationship between the leader and theemployee is well done, employees of EN Mandarin have their responsibility in the company, some employees are satisfiedwith the work given by the company, in the event of compensation partly employees are satisfied with the salary.